Learning Indonesian Culture through an Indonesian TV Series Si Doel Anak Sekolahan - Puji Lestari; Lambok Hermanto Sihombing (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Education broadens students' grasp of all disciplines. Nationalism is one of the most intriguing concerns Indonesian students confront today. Today's students are more technologically savvy, allowing them to get global information quickly. As technology advances rapidly, educators must guide and persuade them to learn more about Indonesian culture. One of the cultures they can learn about is the Betawi culture. Teachers could ask them to learn and read about Indonesian culture using their own devices. However, educators could also assist students through engaging instructional activities, such as watching films about Indonesian culture. 'Si Doel Anak Sekolahan' is the most recommended one. It is one of Indonesian TV series that strongly depicts the life of Betawi culture. Thus, in this study, the researchers aim to analyze how “Si Doel Anak Sekolahan” represents the identity of Betawi culture. The object of this study was taken from RCTI YouTube Channel, Layar Drama Indonesia entitled SI DOEL ANAK SEKOLAHAN - Atun Pengen Kagetin Babe Pake Tanjidor episode 9. To seek how the identity of Betawi culture depicted in that movie, the researchers used a qualitative approach and applied Mise en Scene theory from Manon de Reeper and Cultural Identity theory from Stuart Hall. The result shows that traditional house, oplet, and musical instruments shown in some selected scenes represent Betawi cultural identity.